Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.4049/jimmunol.166.8.5044
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Ability of Pre-TCR and αβTCR to Induce Apoptosis

Abstract: In early CD4−CD8− pro-thymocytes, signaling through the pre-TCR is crucial for survival and differentiation into CD4+CD8+ cells. At this more mature stage, interactions between αβTCR and self-Ag/MHC complexes in turn lead either to cell survival and differentiation (positive selection) or to cell death (negative selection). Intrinsic differences must therefore exist between pre-TCR signals in CD4−CD8− thymocytes and αβTCR signals in CD4+CD8+ cells, since only the latter can mediate a death signal. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…These results are therefore consistent with the notion that the § g TCR and pre-TCR elicit different signals for thymocyte development [12] despite the sharing of several signaling components [33]. However, it remains to be determined whether the difference between the § g TCR and pre-TCR results from the direct recruitment of distinct signaling molecules [34][35][36][37][38], or the differential abilities of pT § and TCR § chain to target the receptor complex to distinct cellular locations [9,11,39], or both.…”
Section: Discussionsupporting
confidence: 86%
“…These results are therefore consistent with the notion that the § g TCR and pre-TCR elicit different signals for thymocyte development [12] despite the sharing of several signaling components [33]. However, it remains to be determined whether the difference between the § g TCR and pre-TCR results from the direct recruitment of distinct signaling molecules [34][35][36][37][38], or the differential abilities of pT § and TCR § chain to target the receptor complex to distinct cellular locations [9,11,39], or both.…”
Section: Discussionsupporting
confidence: 86%
“…4,9,[11][12][13][14][15] Similarly, PGA derivatives are reported to be involved in cell cycle regulation, apoptosis and growth inhibition, not via cytosolic proliferative signaling pathways. 27) While the target molecules or receptors for PGA 2 have not yet been identified, previous reports have shown that PGA 2 induced p21…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] PGA 2 was also shown to induce apoptotic cell death and affect the expression levels of cyclin D1 and p21…”
Section: Screening Of Transactivators For Nor1 Nuclear Receptor By Mamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nurr1 has emerged as a possible target gene in Parkinson's disease (Kim et al 2002), a condition known to be related to differentiation of dopaminergic neurons (Zetterstrom et al 1996b;Saucedo-Cardenas et al 1998); however, roles for Nurr1 in blood cells are almost unknown. On the contrary, there is evidence that Nur77 and NOR1 appear to function similarly in cells, because both molecules reportedly have apoptotic characteristics in immune cells (Cheng et al 1997;Steff et al 2001;He 2002;Winoto and Littman 2002). It follows that they may be implicated in disorders related to genetically or environmentally induced defects of activation-induced cell death (AICD), such as autoimmune diseases.…”
Section: Apoptotic Characteristics Of the Nr4a Nuclear Receptormentioning
confidence: 94%